Modification of cation permeability of rabbit descending colon by sulphydryl reagents. - Luger, A (1981)
1. Addition of the organic mercurials mersalyl, p-chloromercuribenzoate, and p-chloromercuribenzene sulphonate to the Ringer solution (140 mM-Na) bathing the luminal side of isolated epithelia of rabbit descending colon increases short-circuit current (Isc) and tissue conductance (Gt) when the spontaneous Isc is below 2-3 muequiv/cm2 hr. 2. The stimulation of Isc by mersalyl is due to an increase in Na absorption, simultaneously K secretion is induced, whereas Cl absorption is not affected. 3. Mersalyl inhibits Isc at Na concentrations below 50 mM. The Na concentration at which Isc is half-maximal (KNa) is shifted by mersalyl from 25 to 133 mM. The overshoot in Isc to a peak volume of 5 muequiv/cm2 hr observed when Na-depleted tissues are suddenly exposed to Na is markedly depressed by mersalyl. 4. Mersalyl inhibits non-competitively the blocking effect of amiloride on Isc. Both the stimulation of Isc and the inhibition of the amiloride effect by mersalyl have the same time course (half-time of the effects 30-40 min) and similar concentration-response curve (half-maximal effects with 2.0-2.6 x 10(-4) M), indicating a common mechanism. 5. The mersalyl effects on Isc and on the amiloride action are only partially reversed by dimercaptopropanol. p-Chloromercuribenzoate conjugated with dextran (mol. wt. 10,000) elicited the same effects as mersalyl. 6. The stoichiometry of the mersalyl-amiloride interaction, estimated by use of the Hill plot, is 1:1; a Hill coefficient of 1 was also obtained for the stimulating effect of mersalyl on Isc. 7. It is concluded that one sulphydryl group per luminal Na entry site controls both its Na conductance and cation selectivity. Titration of these sulphydryl groups by organic mercurials appear to fix the conductance of the luminal Na entry mechanism in a submaximal position and prevent its modulation by amiloride or variations in intra- and/or extracellular Na concentrations.